2003
DOI: 10.1021/ja034979a
|View full text |Cite
|
Sign up to set email alerts
|

Billion-fold Acceleration of the Methanolysis of Paraoxon Promoted by La(OTf)3 in Methanol

Abstract: The methanolysis of the insecticide paraoxon (2) was investigated in methanol solution containing varying [La(OTf)(3)] (OTf = (-)OS(O)(2)CF(3)) as a function of at 25 degrees C. Plots of the pseudo-first-order rate constants (k(obs)) for methanolysis as a function of [La(OTf)(3)](total) were obtained under buffered conditions from 5.15 to 10.97, and the slopes of the linear parts of these were used to determine the second-order rate constants (k(2)(obs)) for the La(3+)-catalyzed methanolysis of 2. Detailed ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 57 publications
2
73
0
1
Order By: Relevance
“…OMe for this process is 2.6 × 10 −3 dm 3 mol −1 s −1 at 25 °C [29,30]. A subsequent study of the kinetics of the cyclization of 6a-g promoted by the dinuclear Zn(II) complex 8 revealed that the general mechanism involves saturation binding of the substrate to the complex followed by unimolecular decomposition of a 8:6 complex to give the corresponding phenoxide products and the cyclic ester 7 [31] as in eq.…”
Section: The Cleavage Of a Series Of 2-hydroxypropyl Aryl Phosphates mentioning
confidence: 96%
“…OMe for this process is 2.6 × 10 −3 dm 3 mol −1 s −1 at 25 °C [29,30]. A subsequent study of the kinetics of the cyclization of 6a-g promoted by the dinuclear Zn(II) complex 8 revealed that the general mechanism involves saturation binding of the substrate to the complex followed by unimolecular decomposition of a 8:6 complex to give the corresponding phenoxide products and the cyclic ester 7 [31] as in eq.…”
Section: The Cleavage Of a Series Of 2-hydroxypropyl Aryl Phosphates mentioning
confidence: 96%
“…2 is a plot of log k 2 obs determined for cleavage of 3b promoted by [La (III) dimers] at various s s pH values; these kinetic data are overlayed with the speciation diagram of [La 2 (OCH 3 ) n ] (6−n)+ in methanol that was previously determined by potentiometric titration. 17 The plot has a skewed bell-shape profile maximizing at s s pHϳ8.8, suggesting that the the most active species is the dimer [La(OCH 3 ) 2 ] 4+ , although [La 2 (OCH 3 ) 3 ] 3+ also has good activity that is lessened in accordance with its reduced concentration in solution. Similar experiments were performed for the methanolysis of 3 and 4 promoted by 1 at concentrations between 0.175 and 1.75 mmol dm −3 ; the gradients of the k obs versus [1] plots gave the k 2 obs values that are also in Table 1.…”
Section: Kineticsmentioning
confidence: 99%
“…Plot of the first-order rate constant for the methanolysis of 4-nitrophenyl methyl carbonate (3b) catalyzed by added La(Plots of the speciation for La (III) dimers with one to five attached methoxides as a function of s s pH as computed for [La (III) ] total = 2 × 10 −3 mol dm −3 from fits of potentiometric titration data 17. Superimposed on the plots as circles are the k 2 obs data for the La (III) -catalyzed methanolysis of p-nitrophenyl methyl carbonate (3b) determined at various s s pH values, T = 25°C.…”
mentioning
confidence: 99%
“…Метод каталитического метано-лиза предложен канадскими исследователями [1] для эффективной и в то же время достаточно бережной обработки загрязненных поверхностей и позволяет сохранить в рабочем состоянии электронные приборы, оптическую и измери-тельную аппаратуру. В работах [2][3][4][5][6] предложена технология деструкции фосфорорганических пестицидов и имитаторов ФОВ в спиртовой среде в присутствии катализаторов, содержащих ионы металлов.…”
Section: Introductionunclassified